2020
DOI: 10.1108/ssmt-01-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Selective etching and hardness properties of quenched SAC305 solder joints

Abstract: Purpose The purpose of this paper is to investigate the morphology of intermetallic (IMC) compounds and the mechanical properties of SAC305 solder alloy under different cooling conditions. Design/methodology/approach SAC305 solder joints were prepared under different cooling conditions/rates. The performance of three different etching methods was investigated: simple chemical etching, deep etching based on the Jackson method and selective removal of β-Sn by a standard three-electrode cell method. Phase and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The grain boundaries operate as barriers to dislocation migration during load application, increasing the solder alloy's mechanical resistance to deformation (Yahaya et al, 2020). Anyway, a typical strain curve was obtained, as shown in Figure 6(b).…”
Section: Hardness Indentation and Micro-creep Behaviourmentioning
confidence: 98%
See 1 more Smart Citation
“…The grain boundaries operate as barriers to dislocation migration during load application, increasing the solder alloy's mechanical resistance to deformation (Yahaya et al, 2020). Anyway, a typical strain curve was obtained, as shown in Figure 6(b).…”
Section: Hardness Indentation and Micro-creep Behaviourmentioning
confidence: 98%
“…The increase in the hardness value at 0.5 and 1.0 wt.% was mainly because of the strengthening of the grain boundaries by the addition of TiO 2 NPs which coincided with a reduction of the size of the Ag 3 Sn and Cu 3 Sn IMC phases, as shown in Figure 3(c) and 3(e), resulting in more grain boundaries inside the solder matrix. The grain boundaries operate as barriers to dislocation migration during load application, increasing the solder alloy’s mechanical resistance to deformation (Yahaya et al , 2020). Anyway, a typical strain curve was obtained, as shown in Figure 6(b).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Lee and Huang [16] reported that tensile strength and hardness of SAC 305 solder increased at faster cooling rates due to the formation of a fine-grained primary Sn-rich phase surrounded by a fine eutectic structure. Yahaya et al [17] documented the presence of Ag3Sn and Cu6Sn5 phases, with faster solder cooling rates showing the highest hardness values due to phase refinement. The microstructure and mechanical properties of solder alloys are greatly influenced by cooling conditions that affect their reliability [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Yahaya et al [17] documented the presence of Ag3Sn and Cu6Sn5 phases, with faster solder cooling rates showing the highest hardness values due to phase refinement. The microstructure and mechanical properties of solder alloys are greatly influenced by cooling conditions that affect their reliability [16,17]. Refined grains ensure that the internal structure of solder joints is compact and can effectively resist external pressure, thereby improving reliability [18].…”
Section: Introductionmentioning
confidence: 99%